Predicting reading recovery selection and outcomes : is it possible? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education (Literacy) at Massey University, Manawatū, New Zealand - London, Athena (Massey University, 2017)
Purpose: Predictive early literacy assessments are useful to identify students who are at risk of reading difficulty. This study investigated the use of six early literacy assessments, administered when students first entered school (Time 1), and in the middle of their first year at school (Time 2), in order to predict which students would be selected for Reading Recovery and to identify the Reading Recovery (RR) outcomes for students who participated in the intervention. Method: Unpublished data from a longitudinal study (Early Literacy Project, Chapman, Arrow, Tunmer, & Braid, 2016) was analysed to find predictive links between assessment results and later reading outcomes, for a cohort of 300 5-year-old children in New Zealand primary schools. Results: It was not possible to predict which students would be selected for Reading Recovery due to the variations in RR selection processes. It was found that children who participated in RR were more likely to be referred on for further support the lower their phonological awareness scores were. It was also found that if a child scored 20 points or less, in a combination of Time 1 assessments (letter names, letter sounds and three measures of phonological awareness), they were likely to have a body of literacy abilities that meant they would be working at least a year below the National Standard by the end of their second year at school. Implications: The findings indicate that standardising the selection of students for RR may mean students with the lowest literacy attainment all get support. In addition, early literacy assessments, including measures of phonological awareness, should be administered early in a child’s schooling and those identified as being at risk of reading difficulty should receive literacy support without delay. Addressing students’ low levels of phonological awareness in the first year of schooling may lead to better outcomes for students who participate in RR. Keywords: phonological awareness, Reading Recovery, early literacy assessment, letter names, letter sounds, New Zealand, timing of assessment, vocabulary
Keywords: Reading; Ability testing; Remedial teaching; Phonological awareness; Reading Recovery; Early literacy assessment; Letter sounds; Letter names; New Zealand; Timing of assessment; Vocabulary